2014
DOI: 10.1182/blood-2014-04-567057
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alterations of the cohesin complex genes in myeloid malignancies

Abstract: • Recurrent hypomorphic cohesin defects and cohesin low expression were identified in a significant proportion of patients with MDS and AML.• Cohesin mutations likely represent secondary events in clonal hierarchy and contribute to clonal transformation.Somatic cohesin mutations have been reported in myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML). To account for the morphologic and cytogenetic diversity of these neoplasms, a well-annotated cohort of 1060 patients with myeloid malignancies incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
240
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(258 citation statements)
references
References 28 publications
(33 reference statements)
12
240
3
3
Order By: Relevance
“…Importantly, these regions are involved in regulating the expression of genes that govern pluripotency/self-renewal in embryonic stem cells. Therefore, it might be that loss-of-function mutations in cohesin lead to transcriptional alteration of genes that have important roles in differentiation and proliferation, eventually leading to clonal evolution and tumorigenesis [98]. In the case of AML, cohesin mutations lead to loss of chromosome interactions between conserved regulatory elements and promoters at specific hematopoietic genes, such as RUNX1: the deregulation of hematopoietic transcription programs could facilitate the development of AML [96].…”
Section: Mutations Affecting the Cohesin Complexmentioning
confidence: 99%
“…Importantly, these regions are involved in regulating the expression of genes that govern pluripotency/self-renewal in embryonic stem cells. Therefore, it might be that loss-of-function mutations in cohesin lead to transcriptional alteration of genes that have important roles in differentiation and proliferation, eventually leading to clonal evolution and tumorigenesis [98]. In the case of AML, cohesin mutations lead to loss of chromosome interactions between conserved regulatory elements and promoters at specific hematopoietic genes, such as RUNX1: the deregulation of hematopoietic transcription programs could facilitate the development of AML [96].…”
Section: Mutations Affecting the Cohesin Complexmentioning
confidence: 99%
“…Mutually exclusive loss of function nonsense and frameshift mutations in the cohesin components are found in 11% and 17% of low-and high-risk MDS, respectively. 22,23 Cohesin normally functions to align sister chromatids during mitosis; however, mutations do not result in gross aneuploidy. 7,24 Instead, recent studies have shown that cohesin mutations can promote transformation by driving aberrant transcriptional programs, potentially by disrupting this complex's role in stabilizing DNA loops, such as those involved in enhancer-promoter interactions.…”
Section: Cohesinsmentioning
confidence: 99%
“…Interestingly, it has been shown that the cohesin complex could functionally interact with Polycomb group proteins to control gene transcription. 46 It is an interesting observation that ASXL gene mutations 47 as well as cohesin gene mutations 48 are enriched in patients with RUNX1-mutated AML. Recently, several experiments have linked cohesin and RUNX1 in hematopoiesis and leukemogenesis.…”
mentioning
confidence: 99%